2020
DOI: 10.1016/j.jgar.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

An audit of community-acquired pneumonia antimicrobial compliance using an intervention bundle in an Irish hospital

Abstract: Highlights Audit of community-acquired pneumonia (CAP) antimicrobial compliance using an intervention bundle. Intervention bundle including a MARS and promoting access to local CAP guidelines. The intervention bundle can improve antimicrobial stewardship practices and reduce total duration of antibiotics. The intervention bundle can also increase documentation of CURB-65 and uptake of streptococcal urinary antigen testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…13 The 2018 eTG updates saw an increase in high-risk CAP ceftriaxone dosing from 1 g daily to 2 g daily; our findings may reflect either a delay in this change in clinical practice or inadequate CAP risk assessment, which seems to be apparent in other data. 4,5,[10][11][12]14,15 In our cohort, the documented use of any pneumonia severity score was low at 4%. In the Australian studies by Maxwell et and 6%, respectively; the authors argued that this reflected a lack of awareness about this tool.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…13 The 2018 eTG updates saw an increase in high-risk CAP ceftriaxone dosing from 1 g daily to 2 g daily; our findings may reflect either a delay in this change in clinical practice or inadequate CAP risk assessment, which seems to be apparent in other data. 4,5,[10][11][12]14,15 In our cohort, the documented use of any pneumonia severity score was low at 4%. In the Australian studies by Maxwell et and 6%, respectively; the authors argued that this reflected a lack of awareness about this tool.…”
Section: Discussionmentioning
confidence: 60%
“…4,11,12 The most common reason for inappropriate prescribing identified by O'Kelly et al was the overuse of amoxicillin with clavulanate. 10 We similarly found that amoxicillin with clavulanate was the most common non-eTG-recommended antibiotic, despite the eTG advising directly against its use owing to the lower daily dose of amoxicillin, the active component against S. pneumoniae, as compared with amoxicillin 1 g three times daily. 4 In addition to its broader spectrum, this contributes to the development of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations